THE IMPACT OF YEAST NUTRITION ON FLAVOUR FORMATION DURING FERMENTATION - Ribeiro Filho, N. M. (2019)
This thesis generates a knowledge about the role of yeast nutrition on flavour formation during fermentation, specifically related to the influence of essential inorganic elements on yeast-flavour formation. Two yeast nutritional influences, which are total carbohydrates and essential inorganic elements, were considered. Therefore, data were collected to cover five steps, which are divided in 5 result chapters: a characterization of yeast strains (Chapter 3); a more complete understanding of yeast flavour formation (Chapter 4); a new understanding of the role of the essential inorganic element and their effect on yeast-flavour formation during supplemented fermentations (Chapter 5); a creation of a more complete synthetic sweet wort as a tool for fermentation studies (Chapter 6); and finally, a knowledge of the role of inorganic-phosphate, potassium, magnesium as independent variables (input) on flavour formation as dependent variables (output) during alcoholic fermentation using RSM (Chapter 7). All flavour compounds were measured using high-performance liquid chromatography (carbohydrates, ethanol, glycerol and acetic acid) and gas chromatography-mass spectrometry (aromas). Results suggested that alcoholic fermentation can be divided into two domain phases, which are carbohydrates domain and ethanol domain. Carbohydrates phase occurs from the inoculation time to when ethanol concentration became higher than dissolved sugars in wort. During carbohydrate phase, acetic acid was accumulated; in contrast, during ethanol phase, acetic acid was consumed. Acetate esters and fatty acid esters are influenced by carbohydrates domain and ethanol domain; however, most of esters were produced under carbohydrates domain (16h). Afterwards, when singular or a complex mix of eight different essential inorganic elements were added during fermentation, ammonia- nitrogen, inorganic phosphate, potassium and magnesium significantly increased the production of target industrial compounds (ethanol and glycerol) and decreased acetic acid; furthermore increased the formation of higher alcohols and esters. Copper, iron, manganese or a composite mixture of all nutrient supplementations influenced negatively flavour formation. Zinc had less impact on flavour formation. Subsequently, a synthetic sweet wort was developed as a more controllable medium for fermentation studies. To evaluate the interactions among inorganic-phosphate, potassium and magnesium, a RSM was applied. Observed that ethanol is magnesium dependent, yeast growth is potassium/magnesium dependent, and supplementation level of inorganic phosphate, potassium and/or magnesium increase the flavour formation without affect the yeast growth. In conclusion, magnesium is the most important inorganic element for flavour formation (including the formation of ethanol, higher alcohols, acetate esters/fatty acid esters, and off- flavour reduction). Magnesium interacts with phosphorous and potassium as all together acts as important co-factor for fermentation and yeast-flavour formation.